Peripheral Enthesitis Detected by Ultrasonography in Patients With Axial Spondyloarthritis—Anatomical Distribution, Morphology, and Response to Tumor Necrosis Factor-Inhibitor Therapy - Seven, Sengul; Pedersen, Susanne Juhl; Østergaard, Mikkel; Felbo, Sara Kamp; Sørensen, Inge Juul; Døhn, Uffe Møller; Terslev, Lene (Frontiers in Medicine, 2020)
Objectives: To investigate the anatomical distribution, morphological abnormalities and response to adalimumab therapy of ultrasound(US)-detected peripheral enthesitis in patients with axial spondyloarthritis (SpA). Methods: In a randomized, placebo-controlled, double-blinded, investigator-initiated trial(NCT01029847), patients with axial SpA according to the Assessment of Spondyloarthritis International Society criteria were randomized to subcutaneous adalimumab 40 mg every other week or placebo from baseline to week 6. From week 6 to 24, all patients received adalimumab 40 mg every other week. Of 49 patients enrolled, 21 patients participated in our observational US sub-study. US assessment applying the OMERACT US definitions for enthesitis of 10 peripheral entheseal regions of the upper and lower extremities and clinical examination were performed at baseline, weeks 6 and 24. US was performed by one experienced investigator. Hypo-echogenicity, increased thickness and Doppler activity of the enthesis were considered signs of active inflammation, whereas insertional bone erosions, intratendinous calcifications and enthesophytes were regarded as signs of structural lesions. Results: Enthesitis on US was mostly present in the lower limbs, especially in the Achilles tendon(81%), the quadriceps tendon(62%) and the greater femoral trochanter(52%). Structural lesions were predominant(38% vs 12% of examined entheses with inflammatory changes), particularly in the entheses of the lower limbs, and exhibited no change during treatment. Conclusion: US-detected structural lesions were common while inflammatory lesions were relatively rare in patients initiating adalimumab due to axial SpA. Structural lesions did not appear to change during 24 weeks follow-up, suggesting that these lesions may not be helpful outcome measures in short-term clinical trials.